Les reformulations réparatrices dans l’interprétation de conférence - Woroch, Justyna (Studia Romanica Posnaniensia, 2010)
The aim of this paper is to deal with the notion of repair reformulations (fr. reformulations réparatrices) investigated mainly by the conversational analysis researchers but adapted here to the situation of conference interpreting. The author analyses a couple of examples of repairs which appear in the texte produced by the speaker as well as those relevant for the interpreter’s delivery.